Studi Empiris Faktor Diskriminan Tax Avoidance Pada Perusahaan Manufaktur Di Indonesia - Dwi Haryono Wiratno; Rahmawati Hanny Yustrianthe; Maria Purwantini; Ronowati Tjandra (Akademi Akuntansi YKPN Yogyakarta, 2021)
This study aims to determine the effect of Return on Assets (ROA), Debt to Total Assets (DAR), and Corporate Governance (CG) on tax avoidance in manufacturing companies listed on the IDX for the 2015-2019 period. Corporate Governance is proxied by the Composition of the Independent Commissioner, and Tax Avoidance is proxied by the Effective Tax Rate (ETR). The population in this study were 179 companies listed on the IDX. The sample selection used purposive sampling technique and the research sample was obtained as many as 60 companies. The data in this study are secondary data obtained from the official website of the Indonesia Stock Exchange (BEI). The data analysis used is descriptive analysis followed by the requirements test including normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The statistical method used to analyze the data uses multiple linear regression analysis. The results showed that Return on Assets (ROA) had a significant negative effect on tax avoidance. Meanwhile, Debt to Total Assets (DAR) and Corporate Governance (CG), which are proxied by the composition of the independent board of commissioners, have no effect on tax avoidance in manufacturing companies listed on the IDX for the 2015-2019 period.